Rehabilitation of edentulous maxillary arch with hollow denture in an elderly patient with bell's palsy - Vimal Bharathi Bolloju; M Praveen; Sandhya Jadhav; B Ragini; P Parameswar Naishadham (Wolters Kluwer Medknow Publications, 2020)
Retention and stability are the main objectives in a complete denture fabrication. The weight of a maxillary complete denture is one of the factors that affects its retention and stability. Excessive interarch distance between the maxillary and mandibular edentulous arches increases the height and weight of the prosthesis, thus compromising the retention. Long lip length further compromises the situation. This article describes a case report of prosthetic rehabilitation of a patient with bilateral gross asymmetry due to unilateral Bell's palsy and increased prosthetic space by fabricating a light-weighted hollow denture to improve the esthetics and function.